Advanced Materials in 3D/4D Printing Technology - Pan, Houwen Matthew; Luis, Eric (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint contains a collection of state-of-the-art reviews and original research articles from leaders in the field of 3D/4D printing. It focuses on 3D/4D printing materials with novel and/or advanced functionalities, novel applications of 3DP material, and material synthesis and characterization techniques.